2015
DOI: 10.1080/21639159.2015.1043690
|View full text |Cite
|
Sign up to set email alerts
|

SNS users' para-social relationships with celebrities: social media effects on purchase intentions

Abstract: In this study, the authors investigate factors that influence para-social relationships between social network service (SNS) users and celebrities and the effects on users' purchase intentions. The study shows that SNS use and para-social relationships with celebrities are positively related. User/celebrity para-social relationships and celebrity reputation also show positive relationships with purchase intentions. Gender differences affect relationships between celebrity reputation, para-social relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 55 publications
7
72
0
6
Order By: Relevance
“…Within the tourism industry, emphasis on pop culture involvement is increasing more than ever due to the development of modern media (Gross & Brown, 2006;Kim, Ko, & Kim, 2015). Consumers can now access pop culture more easily and they can also easily find cases showing the effect of pop culture on tourism.…”
Section: Pop Culture Involvementmentioning
confidence: 98%
“…Within the tourism industry, emphasis on pop culture involvement is increasing more than ever due to the development of modern media (Gross & Brown, 2006;Kim, Ko, & Kim, 2015). Consumers can now access pop culture more easily and they can also easily find cases showing the effect of pop culture on tourism.…”
Section: Pop Culture Involvementmentioning
confidence: 98%
“…For instance, Lim and Kim () found that consumers who developed parasocial interactions with TV shopping hosts are likely to have higher levels of shopping satisfaction. Similarly, consumers were found to have positive attitudes toward products (Knoll, Schramm, Schallhorn, & Wynistorf, ) and strong intentions to purchase them (Kim, Ko, & Kim, ) when the products were endorsed by celebrities with whom consumers had built parasocial relationships. Labrecque () examined parasocial relationships between consumers and brands, and found that parasocial relationships lead to brand loyalty and willingness to provide personal information to brands in Web site forms and customer surveys.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Weibo (referred to as "Chinese Twitter") has reached a total of 486 million monthly active users by the end of June 2019 and gradually transformed from a simple microblogging platform to the biggest integrated SNS in China [25] . And notable features of Weibo, include 1) supporting interactive two-way communication with celebrities; 2) diverse and customized celebrities marketing strategies; 3) "Super Topics" (the specific function of Weibo that demonstrates equally shared hot debated subject online that help users to have real-time immersive communication with other like-minded members [27,29] ) and thriving virtual communities [26] .…”
Section: Online Interaction (Oi) and The Intensity Of Oi On Weibomentioning
confidence: 99%
“…Particularly, the quality and frequency of commenting and continuing interaction with a celebrity can be indicators of celebrities' marketing power. If fans are interested in or attracted by the marketing messages on a celebrity's social media feed, they are likely to forward the post, which could snowball in user's community network, and subsequently boost the viral power and marketing impact of a celebrity [29] .…”
Section: Online Interaction (Oi) and The Intensity Of Oi On Weibomentioning
confidence: 99%